Awareness Regarding Stroke among the Adult Population of Gokarneshwor Municipality - Sapkota, Abja; Devkota, Sabitra (Nepal Medical College Journal, 2024)
A stroke is a medical emergency that occurs as a result of decreased blood supply or cessation of blood flow to the brain. Even though there are preventable risk factors still, it is one of the leading causes of disability worldwide. Awareness of the risk factors and early recognition of the symptoms can help the prevention and management of stroke. This study was conducted with an aim of assessing the awareness regarding stroke among adult population residing at Gokarneshwor Municipality. A descriptive cross-sectional study was conducted among 195 adult populations using a non-probability convenience sampling method. Data was collected by face-to-face interview technique with the self-constructed questionnaire. Data were entered and analyzed using the SPSS-16. Descriptive statistics like frequency, percentage, and inferential statistics such as the chi-square test were used and were considered significant at p< 0.05 (95% CI). The mean age of the respondents was 36.01±12.66 years. Of all, hypertension was prevalent in 32 respondents. Almost three fourth of the participants had heard about stroke. Top three stated risk factors were hypertension, alcohol consumption, and smoking. We concluded that providing informal education and conducting awareness programs on stroke would be helpful to promote awareness regarding this condition.